A study on the relationship between stock market in developing countries to the gold price (India, China and Malaysia) - Abdul Ghafar, Mohd Azamudin (2012)
This paper attempts to investigate the relationship between Bombay Stock Exchange Index, Shanghai Stock Exchange Index and FTSE Malaysia Index to the FTSE Gold Mines Index. The weekly data of closing price of stock indices and gold prices from 1st January 2007 to 31st December 2011 are collected. The study used Simple Linear Regression and Multiple linear Regression in order to find the relationship among markets. From the result, it shows significant relationship between Bombay Stock Exchange Index, Shanghai Stock Exchange Index and FTSE Malaysia Index to the FTSE Gold Mines Index. In other hand, low and negative correlation exist in these three stocks indices to the gold prices. It means gold serves as a diversification asset in Shanghai Stock Exchange Index and FTSE Malaysia Index but the gold price can be tools to predict the Bombay Stock Exchange Index because there have positive relationship. Finally, this research will be useful for market analysts and investor to have a better understanding on the role of gold as a safety investment.